E-Learning in Pharmacology and Pharmacy - Thomas Efferth (MDPI AG, 2011)
Computer-based learning facilitates a shift from externally controlled to self-directed learning. Universities and other educational institutions are challenged by these developments and must react appropriately to meet the requirements of education. The term e-learning has been coined to describe a wide range of diverse learning and teaching strategies based on the use of electronic devices. Recently developed concepts in the science of education and learning provide appropriate frameworks for novel e-learning scenarios. The present review introduces strategies and concepts for the implementation of e-learning in academic and non-academic programs and gives an overview of current e-learning activities in pharmacology.